A taxonomic review of the southern African millipede genus, Bicoxidens Attems, 1928 (Diplopoda: Spirostreptida: Spirostreptidae), with the description of three new species and a tentative phylogeny - Mwabvu, Tarombera; Hamer, Michelle L.; Slotow, Robert H. (Zootaxa, 2007)
The eight species of Bicoxidens were studied in order to verify their taxonomic validity and determine the status of new material. Two new synonymies are established: B. grandis Lawrence, 1965 = B. matabele (Schubart, 1966) and B. flavicollis Attems, 1928 = B. nasti Mwabvu, 2000. B. polyptychus, incorrectly placed in Bicoxidens, on the basis of morphological characters, including gonopods, is moved to Brevitibius Attems, 1950. Three new species, B. matopoensis Mwabvu, B. nyathi Mwabvu and B. gokwensis Mwabvu are described. An identification key to the species, a phylogenetic analysis based on gonopod morphology and distribution data for each species are also presented